Cornus Officinalis Polyphenol Extract Decrease Pro-inflammatory Markers in Lipopolysaccharide (LPS)-induced RAW 264.7 Macrophages (P06-087-19). (13th June 2019) - Najjar, Rami; Akhavan, Neda; Pourafshar, Shirin; Hsieh, Yun-Hwa; Arjmandi, Bahram; Feresin, Rafaela
Abstract: Objectives: To investigate whether cornus officinalis (CO) polyphenol extract attenuate the inflammatory response induced by lipopolysaccharide (LPS) in RAW 264.7 macrophages. Methods: CO polyphenol extract was prepared using methanolic extraction, followed by solvent evaporation and freeze-drying. RAW 264.7 macrophages were treated with 0, 50, 100, 200 and 400 μg/ml of CO polyphenol extract. After 2 h, cells were then treated with 100 ng/ml of LPS for 6 h. Cells were then collected for whole cell protein expression analysis of signaling and inflammatory molecules via western blot. Results were analyzed using ANOVA followed by Tukey-Kramer post-hoc test. Results: LPS treatment significantly increased Akt phosphorylation compared to control (1.00 ± 0.00 vs 0.16 ± 0.02 fold, P < 0.0001). However, pre-treatment with 100, 200 and 400 µg/ml of CO polyphenol extract significantly reduced Akt phosphorylation (0.57 ± 0.08 fold, P = 0.0030; 0.49 ± 0.08 fold, P = 0.0003 and 0.44 ± 0.09 fold, P < 0.0001, respectively) in LPS stimulated macrophages compared to LPS alone. Control cells did not express inducible nitric oxide synthase (iNOS); however, LPS induced iNOS expression, which was significantly decreased by treatment with 400 µg/ml CO polyphenol extract (1.00 ± 0.00 vs 0.36 ± 0.1 fold, P = 0.0098). Similarly, inflammatory cytokines such as interleukin (IL)-1β and 6 were not expressed in control macrophages; however, their expression was induced by LPS. CO polyphenol extract dose-dependently decreased LPS-induced expression of IL-1β ( P < 0.0001) and IL-6 ( P < 0.0001). Conclusions: CO polyphenol extract attenuated the inflammatory response induced by LPS in RAW 264.7 macrophages. This effect is likely due to Akt downstream signaling inhibition. Funding Sources: Lewis Foundation Grant Program.